A SCIENTIFIC STUDY OF THE SUFI TAFSIRS WRITTEN IN MAWARAUNNAHR (The Journal of Interdisciplinary Human Studies, 2026)
The article analyzes the formation and development of Sufi Qur’anicexegesis and its esoteric (ishari) interpretations based on historical sources. Thestudy examines Najm al-Din Kubra’s Ta’wilat Najmiyya, the esoteric commentariescontinued by Simnani, as well as the methods of Qashani and other prominent Sufiexegetes through a comparative approach. It also discusses the theoretical foundationsof ishari exegesis, the emergence of symbolic interpretation, and its influence on latergenerations of Sufi commentators.The article further investigates major Persian and Arabic Sufi tafsirs producedin the region of Mawarannahr, including Khoja Porsa’s Tafsiri Qur’on and Charxi’sTafsiri Charxi. Their manuscript copies, structure, stylistic features, and significancewithin the tradition of Sufi Qur’anic interpretation are examined in detail.The findings show that ishari tafsirs first emerged within oral traditions and laterdeveloped into independent written works. Their primary aim was to interpret theinner meanings of Qur’anic verses in harmony with spiritual and ethical principles.The conclusion emphasizes the importance of Sufi tafsirs as a distinct school withinQur’anic interpretation, their impact on later exegetes, and their enduring scholarlyvalue
Keywords: Sufi exegesis; ishari tafsir; Ta’wilat Najmiyya; Najm al-Din Kubra; Simnani; Qashani; symbolic interpretation; Sufi hermeneutics; Persian tafsir; Central Asian Qur’anic commentary